Prise En Charge Infirmière De La Douleur Chez L’adulte Au CHU-Kara (Togo) - Prénam, Houzou; Kodjo, Kakpovi; Komi, Amanga; Essodjêlina, Amana; S., Dake Kodjo; Arafat, Dodja; Salifou, Ibrahime; Kantame, Sandante; Eyram, Fianyo; ES., Koffi-Tessio Viwalé; Owonayo, Oniankitan; Moustafa, Mijiyawa (European Scientific Journal, ESJ, 2018)
Introduction: Pain is a frequent reason for consultation in health facilities. Thus, nurses are in the forefront in the fight against pain. The aim of this study was to determine the role of the nurse in the management of the painful adult patient. Methodology: It was a cross-sectional study conducted in 11 departments of Kara teaching hospital during two weeks. Nurses who had managed a painful adult in the past seven days were included in the study. Results: Thirty nurses participated in the study. They were made of 24 men (76.67%) and six women (23.33%). The average age of nurses was 35 years (extremes: 23 years old and 50 years old) and 43.33% of them had less than five years of work experience. The main etiologies of pain managed were: trauma (22%), headache (18%) and abdominal pain (14%). Pain assessment tools were almost non-existent. Fifty percent of nurses did not know pain assessment tools. The evaluation of pain was performed with conventional tools by 16% of nurses. The analogical visual scale was the most used (three out of five nurses). Nursing intervention was dominated by counseling (43%) and thermal stimulation (22%). The use of analgesics was carried out in 83.33% of cases. Conclusion: This study shows that few nurses evaluated the pain during its management in adults. Therefore, it is necessary to initiate medical training for Togolese nurses on the management of the painful patient in order to make them more effective.